Ensuring a Turning Point with Political Ideology and Cultural Knowledge to Achieve the 2045 Vision - Mansurni Abadi; Nicho Hadi Widjaja; Shahrial Bin Ishak; Peter Olausson (Pancasila: Jurnal Keindonesiaan, 2022)
The literature analyzing perspectives on Indonesia's golden years in the 2045 narrative is extensive and optimistic. But achieving 2045 is more challenging amid disruption conditions, especially after a multidimensional crisis because of COVID-19. Cite Sukarno's term about the years of Vivere Pericoloso, an Italian phrase that means life is full of danger, making our future toward 2045 uncertain. But the years of Vivere Pericoloso are also the right moment to perfectly achieve the ideals, principles, goals, efforts, and logic of the Indonesia 2045 vision. Culture and politics are two important components that can make our turning point toward 2045 come true. Our findings are political ideology based on expansive penetration with internalization and consistency using indoctrination method toward "Pancasila" itself via youth’s empowerment with the principle of fair and open involvement in the political sphere, and strengthening political literacy plays a critical role in dealing with tech populism and non-integrity that created de-stabilization and incompetence. Cultural knowledge that is based on a sense of belonging with an intercultural bond strategy is also important. In practice, cultural knowledge encourages us to act with positive impacts on multicultural society amidst the post-truth era through: (1) awareness of cultural worldview, (2) good attitude toward cultural differences, (3) knowledge of different cultural practices and worldviews, including having the skill of cultural sensitivity awareness, and (4) cross-cultural skills communication.